Performance Modelling of Co-Fired Palm Kernel Shell -Pulverized Coal Blend in Steam Power Plant - O. O. Ighodaro; F. E. Ndem (Journal of Applied Sciences and Environmental Management, 2023)
This study investigates the performance of co-firing palm kernel shell (PKS) and pulverized coal in a steam power cycle. The process simulation software Aspen Hysys was used in the simulation. The study analyzed the various emitted combustion product gases. The cycle efficiency and Power output for each fuel sample blend was carried out.  This provided the basis for the performance comparison of each fuel sample. The Sample D with mix ratio 80 (coal)-20 (PKS) came out the best fuel blend having a CO2 emission of 1844.198854 Kgmol/h, an SO2 emission of 8.830612928 kgmol/h, a cycle efficiency of 0.41 and an estimated power of 104, 076 kW.  It was concluded that coal blended with palm kernel shell at a mix ratio of 80-20 has a suitable heating value for steam generation which promotes a cleaner coal usage with a significant reduction in the emission levels of greenhouse gases.